Meaning's Comparison of Two Autumn Haiku Written by Masaoka Shiki and Takarai Kikaku - Zaki Ainul Fadli; Najma Fairus Handoko (IZUMI, 2021)
Every country has its own culture. Japan has a close culture of art, both modern and traditional. One of the Japanese arts in literature is poetry. Poetry in Japanese literature is called haiku. To find out the differences and similarities in the meanings contained in the autumn-themed haiku by Masaoka Shiki and Takarai Kikaku, the writer intends to analyze the comparison of the two-autumn haiku by Masaoka Shiki and Takarai Kikaku. Comparative analysis of meaning is studied using Ronald Barthes's semiotic study to find its meaning. The semiotic study used is Ronald Barthes's semiotics which uses two stages of study through denotation and connotation, then its relationship with myth or culture. The result of this research produces a comparison of the similarities and differences between Masaoka Shiki's autumn haiku and Takarai Kikaku's. The similarity of autumn haiku by Masaoka Shiki and Takarai Kikaku is the theme raised, namely the beauty of nature and the environment. While the difference between the autumn haiku by Masaoka Shiki and Takarai Kikaku is the philosophical meaning of the discussion, and in the background of time and atmosphere mentioned.